Challenges Faced by English Tutors in Teaching EYL through Online - Kamilah, Nahdhiyatun; Elfiyanto, Sonny (ELLITE, 2023)
The government urged people to study and work from home at the beginning of March 2020 due to Covid-19 spreading in Indonesia; however, online learning has become very popular today. It is proven by many English courses in Pare provide online classes. One program that people are interested in is English for Kids. The previous study found that online teaching to English Young Learners (EYL) is not that easy; therefore, it has not been found a study to explore the challenges English tutors face in teaching online to EYL. The participants of this study were seventy-five tutors who teach EYL encountered online English courses in Pare. The researchers employed a descriptive quantitative approach. The data was collected through a questionnaire that consisted of 21 items and three open-ended questions. The data were analyzed by using the Likert scale. The findings of this research show that electricity failure and poor internet connectivity become crucial challenges. The students that are assisted by their parents also make tutors seem challenged in teaching EYL. Irregularly, the students feel bored in learning English through online. Although some tutors never join any workshop on Teaching English for Young Learners, they are good at giving guidance to teach young learners.